2011
DOI: 10.1177/1934578x1100600118
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Biochemical Characterization of 5′-Phosphodiesterase and Phosphomonoesterase from Barley Malt Sprouts

Abstract: A comparative biochemical characterization is described of two competing enzymes in the production of flavoring 5'-ribonucleotides, barley malt sprouts 5'-phosphodiesterase (5'-PDE) and phosphomonoesterase (PME). Fractionation of these two enzymes and partial purification of 5'-PDE were achieved by a combination of thermal treatments and precipitation with acetone. With synthetic substrates, under standard assay conditions, 5'-PDE and PME had maximum activities at pH 8.9, 70ºC and 55ºC, and K m of 0.26 mM and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
1
6
0
2
Order By: Relevance
“…3 beer barley rootlets by gel filtration on Sephadex G-25 and Sephadex G-75. The enzymatic properties of these 5'-PDEs were similar to those of some reported barley enzymes [9,13,15]. The enzymes can be applied for hydrolysis of RNA to produce flavor nucleotides.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…3 beer barley rootlets by gel filtration on Sephadex G-25 and Sephadex G-75. The enzymatic properties of these 5'-PDEs were similar to those of some reported barley enzymes [9,13,15]. The enzymes can be applied for hydrolysis of RNA to produce flavor nucleotides.…”
supporting
confidence: 73%
“…Compared with many other sources, barley malt rootlets are cheaper materials for the preparation of 5'-PDE, and additionally, there is no doubt about the safety of the enzyme. Hence, there has been a steady growth of interest in the purification and characterization of 5'-PDE from barley malt rootlets [9][10][11][12]. Reports [13,14] showed that the enzyme extracts prepared from malt rootlets contain not only nucleases, including 5'-PDE, but also phosphatases, which can cause further hydrolysis of 5'-nucleotides, and make the crude extracts unsuitable for use in preparing 5'-nucleotides from RNA.…”
mentioning
confidence: 99%
“…Additionally, further attention has been focused on the use of such cereal by‐products as ingredients in foods. Examples include applications of malt rootlets in bread, biscuits and sausages, for enzyme isolation, polyphenol/antioxidant extraction and exogenous enzyme production, among others . To consider their use in human food products, rootlet and fermented rootlet composition in addition to their behaviour in food systems must be evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Hua and Huang (2010), in their recent study, found 5'-PDE from barley rootlets to be stable at 70°C for 420 minutes. On the other hand, Beluhan and Maric (2011), in their work on 5'-PDE from barley rootles, observed retention of 70% relative activity after 120 min of incubation at 70°C. Besides that, 5'-PDE from yeast extract, which has an optimum temperature of 65°C, showed decreasing stability with an increase in temperature (Sombutyanuchi et al, 2001).…”
Section: Temperature Optimum and Stabilitymentioning
confidence: 95%